Villainage in England Essays in English Mediaeval History - Vinogradoff, Paul (Cambridge library collection. Medieval History, 1892)
Russian historian and jurist Sir Paul Vinogradoff (1854–1925) maintained throughout his life a serious scholarly interest in the history of Great Britain, his adopted country. Elected to a professorship at Oxford in 1903, to the British Academy in 1905, and knighted for services to the realm in increasing Anglo-Russian understanding during the war (1917), Vinogradoff demonstrates in this book of 1892 both his interest in feudal England and his historiographic approach, which relied on detailed research using primary sources to examine individuals, communities, and social structures. Divided into two essays - 'The Peasantry of the Feudal Age' and 'The Manor and the Village Community' - the work used England's extensive feudal records to draw a general character of the period. Villainage will interest students of English or European mediaeval history and scholars of mediaeval legal history and of developments in nineteenth-century historiography